Wheat Leaf Rust Effector Pt48115 Localized in the Chloroplasts and Suppressed Wheat Immunity - Lulu Song; Liping Cui; Hao Li; Na Zhang; Wenxiang Yang (Journal of Fungi)
Wheat leaf rust caused by Puccinia triticina (Pt) is a prevalent disease worldwide, seriously threatening wheat production. Pt acquires nutrients from host cells via haustoria and secretes effector proteins to modify and regulate the expression of host disease resistance genes, thereby facilitating pathogen growth and reproduction. The study of effector proteins is of great significance for clarifying the pathogenic mechanisms of Pt and effective control of leaf rust. Herein, we report a wheat leaf rust candidate effector protein Pt48115 that is highly expressed in the late stages of infection during wheat–Pt interaction. Pt48115 contains a signal peptide with a secretory function and a transit peptide that can translocate Pt48115 to the host chloroplasts. The amino acid sequence polymorphism analysis of Pt48115 in seven different leaf rust races showed that it was highly conserved. Pt48115 inhibited cell death induced by Bcl-2-associated X protein (BAX) from mice or infestans 1 (INF1) from Phytophthora infestans in Nicotiana benthamiana and by DC3000 in wheat, and its 145–175 amino acids of the C-terminal are critical for its function. Furthermore, Pt48115 inhibited callose deposition and reactive oxygen species accumulation in the wheat cultivar Thatcher, demonstrating that it is an effector that enhances Pt virulence by suppressing wheat defense responses. Our findings lay a foundation for future studies on the pathogenesis of Pt during wheat–fungus interaction.